1989
DOI: 10.1159/000181276
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Parathyroid Adenoma Volume and Biochemical Function

Abstract: We retrospectively studied data of 24 patients with surgically proven hyperparathyroidism to determine whether biochemical function correlated with the calculated volume of parathyroid adenoma. Carboxyl-terminal parathyroid hormone (C-PTH), amino-terminal parathyroid hormone (N-PTH), nephrogenous cyclic AMP (N-CAMP), and other markers of calcium metabolism were measured with standard techniques. Tumors were divided into small ( < 1.0 cm3) or large (≧1.0 cm3) sizes. N-PTH and C-PTH measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
7
1
Order By: Relevance
“…A number of previous studies have attempted to quantify the relationship between the biochemical markers of hyperparathyroidism and parathyroid adenoma size and volume with mixed results. A literature search revealed eight previous studies comparing size of adenomas to preoperative calcium or parathyroid hormone levels 7–14 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of previous studies have attempted to quantify the relationship between the biochemical markers of hyperparathyroidism and parathyroid adenoma size and volume with mixed results. A literature search revealed eight previous studies comparing size of adenomas to preoperative calcium or parathyroid hormone levels 7–14 …”
Section: Discussionmentioning
confidence: 99%
“…Rutledge et al 7 found a statistically significant but weak correlation ( r = 0.16; Pearson's coefficient) between adenoma weight and preoperative [Ca] and [PTH], while Dubost, 8 Wagner, 9 Saadeh 10 and Williams 11 found no relationship between serum calcium and PTH levels and adenoma weight or volume, although these studies did not specifically exclude patients with parathyroid hyperplasia, double adenomas, renal hyperparathyroidism, and parathyroid carcinoma. A recent study of 63 single adenomas by Bindlish et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations